Lembaga pendidikan dalam peradaban Islam - Muhtarom, Dede Ahmad; Triyanto, Agus; Syafri, Ulil Amri; Handrianto, Budi (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2023)
An educational institution is an institution or place where educational processes take place with the aim of changing individual behavior in a better direction through interaction with the surrounding environment. An Islamic educational institution is a place or organization that organizes the implementation of Islamic education. Therefore, these institutions must be able to create an atmosphere that allows for the implementation of education properly according to the tasks assigned to them, such as schools (madrasas) that carry out the process of Islamic education. There are three types of Islamic educational institutions: Formal Institutions, Non-Formal Institutions, and Informal Institutions. A formal institution is a structured and tiered educational pathway consisting of basic, secondary, and higher education. Meanwhile, the non-formal institution is an educational pathway outside of formal education that is carried out in a structured and tiered manner. This non-formal education institution is provided for a student who does not have time to attend or complete a certain level of formal education. While informal educational institutions are education that focuses more on the family and community. Abstrak         Lembaga pendidikan adalah lembaga atau tempat berlangsungnya proses pendidikan yang dilakukan dengan tujuan untuk mengubah tingkah laku individu ke arah yang lebih baik melalui interaksi dengan lingkungan sekitar. Lembaga pendidikan Islam adalah tempat atau organisasi yang menyelenggarakan pendidikan Islam, yang mempunyai struktur yang jelas dan bertanggung jawab atas terlaksananya pendidikan Islam. Oleh karena itu, lembaga pendidikan Islam tersebut harus dapat menciptakan suasana yang memungkinkan terlaksananya pendidikan dengan baik, menurut tugas yang diberikan kepadanya, seperti sekolah (madrasah)yang melaksanakan proses pendidikan Islam ada tiga macam lembaga pendidikan Islam, yaitu Lembaga Pendidikan Islam Formal, Lembaga Pendidikan Islam Non Formal, dan Lembaga Pendidikan Islam Informal. Lembaga pendidikan formal adalah jalur pendidikan yang terstruktur dan berjenjang yang terdiri atas pendidikan dasar, pendidikan menengah, dan pendidikan tinggi. Sedangkan Lembaga pendidikan non formal adalah jalur pendidikan di luar pendidikan formal yang dilaksanakan secara terstruktur dan berjenjang. Lembaga pendidikan nonformal ini disediakan bagi warga yang tidak sempat mengikuti atau menyelesaikan pendidikan pada jenjang tertentu dalam pendidikan formal. Sedangkan lembaga pendidikan informal adalah pendidikan yang ruang lingkupnya lebih terarah pada keluarga dan masyarakat.